Galectin-3 predicts cardiovascular events in patients with type-2 diabetes. (25th November 2020) - Lorenzo-Almoros, A; Pello, A; Acena, A; Martinez-Milla, J; Tarin, N; Cristobal, C; Blanco-Colio, L.M; Martin-Ventura, J.L; Huelmos, A; Gutierrez-Landaluce, C; Lopez-Castillo, M; Alonso, J; et al.
Abstract: Introduction: Type-2 diabetes mellitus (T2DM) is associated with early and severe atherosclerosis. However, few biomarkers can predict cardiovascular events in this population. Methods: We followed 964 patients with coronary artery disease (CAD), assessing at baseline galectin-3, monocyte chemoattractant protein-1 (MCP-1) and N-terminal fragment of brain natriuretic peptide (NT-proBNP) plasma levels. Secondary outcomes were acute ischemia and heart failure or death. Primary outcome was the combination of the secondary outcomes. Results: Male patients were 75.0% in T2DM and 76.6% in the non-T2DM subgroup (p=0.609). Age was 61.0 (54–72) and 60.0 (51–71) years, respectively (p=0.092). 232 patients had T2DM. Patients with T2DM showed higher MCP-1 [144 (113–195) vs. 133 (105–173) pg/ml, p=0.006] and galectin-3 [8.3 (6.5–10.5) vs. 7.8 (5.9–9.8) ng/ml, p=0.049] levels. Median follow-up was 5.39 years (2.81- 6.92). Galectin-3 levels were associated with increased risk of the primary outcome in T2DM patients [HR 1.57 (1.07–2.30); p=0.022], along with a history of cerebrovascular events. Treatment with clopidogrel was associated with lower risk. In contrast, NT-proBNP and MCP-1, but not galectin-3, were related to increased risk of the event in non-diabetic patients [HR 1.21 (1.04–1.42); p=0.017 and HR 1.23 (1.05–1.44); p=0.012, respectively], along with male sex and age. Galectin-3 was also the only biomarker that predicted the development of acute ischemic events and heart failure or death in T2DM patients, while in non-diabetics MCP-1 and NT-proBNP, respectively, predicted these events. Conclusion: In CAD patients, cardiovascular events are predicted by galectin-3 plasma levels in patients with T2DM, and by MCP-1 and NT-proBNP in those without T2DM. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Insituto de Salud Carlos III